2021
DOI: 10.1002/cey2.98
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the improved performance of sulfur‐doped interconnected carbon microspheres for Na‐ion storage

Abstract: As one of the low-cost energy storage systems, Na-ion batteries (NIBs) have received tremendous attention. However, the performance of current anode materials still cannot meet the requirements of NIBs. In our work, we obtain sulfur-doped interconnected carbon microspheres (S-CSs) via a simple hydrothermal method and subsequent sulfurizing treatment. Our S-CSs exhibit an ultrahigh reversible capacity of 520 mAh g -1 at 100 mA g -1 after 50 cycles and an excellent rate capability of 257 mAh g -1 , even at a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Regrettably, it has been demonstrated that the graphite anode commonly used in LIBs exhibits poor electrochemical performance for Na‐ion batteries (NIBs) 4–6 . Therefore, current researches on NIBs are mainly focused on some new anode materials with better electrochemical performance 7,8 . Moreover, owing to the relatively high standard hydrogen potential of Na compared with Li, NIBs also present a relatively low energy density 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, it has been demonstrated that the graphite anode commonly used in LIBs exhibits poor electrochemical performance for Na‐ion batteries (NIBs) 4–6 . Therefore, current researches on NIBs are mainly focused on some new anode materials with better electrochemical performance 7,8 . Moreover, owing to the relatively high standard hydrogen potential of Na compared with Li, NIBs also present a relatively low energy density 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It is critical to developing suitable electrode materials with the ability to accommodate highly reversible Na + intercalation/deintercalation in obtaining high-performance SIBs because of the large ionic radius of Na + . [5][6][7][8] Cathode materials, functioning as Na + suppliers, significantly affect the cost and comprehensive performance of battery. [9,10] Research has been carried out on diverse cathode materials, where layered metal oxides are mainly included, and Prussian blue compounds, polyanionic and Na 0.5 Ni 0.05 Co 0.15 Mn 0.65 Mg 0.15 O 2 (LLS-NaNCMM15) for SIBs, which were synthesized through a simple thermal polymerization method.…”
Section: Introductionmentioning
confidence: 99%
“…Seeking a kind of energy storage technology with low cost and high efficiency becomes necessary. [5][6][7] As potential energy storage technology, K-ion batteries (KIBs) have been favored by researchers due to their abundant K resources and low cost. [8][9][10] However, the excessively large K-ion radius leads to slow kinetics and large volume changes of anode materials during the potassiationdepotassiation process, resulting in rapid capacity decay in KIBs.…”
Section: Introductionmentioning
confidence: 99%